Determining Ribavirin's mechanism of action against Lassa virus infection - Carrillo-Bustamante, Paola; Thi Huyen Tram Nguyen; Oestereich, Lisa; Guenther, Stephan; Guedj, Jeremie; Graw, Frederik (Scientific Reports, 2017)
Ribavirin is a broad spectrum antiviral which inhibits Lassa virus (LASV) replication in vitro but exhibits a minor effect on viremia in vivo. However, ribavirin significantly improves the disease outcome when administered in combination with sub-optimal doses of favipiravir, a strong antiviral drug. The mechanisms explaining these conflicting findings have not been determined, so far. Here, we used an interdisciplinary approach combining mathematical models and experimental data in LASV-infected mice that were treated with ribavirin alone or in combination with the drug favipiravir to explore different putative mechanisms of action for ribavirin. We test four different hypotheses that have been previously suggested for ribavirin's mode of action: (i) acting as a mutagen, thereby limiting the infectivity of new virions; (ii) reducing viremia by impairing viral production; (iii) modulating cell damage, i.e., by reducing inflammation, and (iv) enhancing antiviral immunity. Our analysis indicates that enhancement of antiviral immunity, as well as effects on viral production or transmission are unlikely to be ribavirin's main mechanism mediating its antiviral effectiveness against LASV infection. Instead, the modeled viral kinetics suggest that the main mode of action of ribavirin is to protect infected cells from dying, possibly reducing the inflammatory response.
CRIS-Team Scopus Importer:2022-12-14